Predictive value of serum proinflammatory biomarkers in respiratory infections in children and clinical-therapeutic correlations - Titiana Cornelia Cotoi; Raluca Niculescu; Adrian-Horațiu Sabău; Lorena Meliț; Oana Cristina Mărginean; Adina Huțanu; Daniela Lucia Muntean (Amaltea Medical Publishing House, 2020)
Introduction. Pneumonia in children causes a high rate of morbidity and mortality, especially in young children. The evolution and prognosis are influenced by a series of clinical-biological parameters, in relation to the child's age and the therapy received. Objectives. Assessment of proinflammatory status in patients with pneumonia. Material and methods. The study was conducted at the Pediatrics Clinic I within the Emergency County Clinical Hospital in Tg. Mures, Romania, between September 2018 and December 2019 and included 95 patients. Results. Analysis of the serum level of C-reactive protein, the high-sensitive form (hsCRP), showed a positive correlation, statistically significant between its level at admission and the number of neutrophils at admission (p = 03169, r = 0.2801), respectively a negative correlation, statistically significant between its level at discharge and the level of leukocytes (p = 0.0253, r = -0.2911), monocytes (p = 0.0014, r = -0.4105) and neutrophils (p = 0.0335, r = -0.2793) at discharge. From the three monitored cytokines (IL-1β, IL-6 and TNF-α) statistically significant correlations were observed for TNF-α. Thus, a positive, statistically significant correlation was identified between lymphocyte values (p = 0.0007, r = 0.3448), monocytes (p = 0.00563, r = 0.2896) and platelets (p = 0.0335, r = 0.2195) at admission with the values of the serum marker TNF-α. Also, a negative, statistically significant correlation was identified between hemoglobin values (p = 0.0034, r = -0.328) and hematocrit (p = 0.0004, r = -0.3932) at discharge and the TNF-α serum marker values. The following correlations were observed: negative correlation, statistically significant between TNF-α and NLR (p = 0.0144, r = -0.2601), NPR (p = 0.0473, r = -0.2051) and PLR (p = 0, 0138, r = -0.2602), positive correlation, statistically significant between hsCRP at admission and NLR (p = 0.0124, r = 0.3264), NPR (p = 0.0073, r = 0.3460) and positive correlation, statistically significant between hsCRP at discharge and NLR (p = 0.0189, r = 0.3128), PLR (p = 0.0036, r = 0.3831). Conclusions. Our study showed that the values of neutrophils, lymphocytes, monocytes and platelets, NLR, PLR and TNF-α were significantly increased in pneumonia, correlating with C-reactive protein, highlighting the early inflammatory status in this condition.